Distinct molecule adsorption behaviors on warped nanographene C80H30: A theoretical study. (April 2016) - Dai, Yafei; Li, Zhenyu; Yang, Jinlong
Abstract: Adsorption of small molecules, such as O2, H2, CO, NO, NH3, HCHO, and SO2, on a recently synthesized warped nanographene C80 H30 is investigated in the framework of density functional theory (DFT). Except for O2, all these molecules are physically adsorbed on C80 H30, typically with very small adsorption energies. However, SO2 adsorption has a relatively large adsorption energy accompanied with a notable charge transfer between adsorbate and substrate. This result makes C80 H30 a potential SO2 chemical sensor. O2 can be chemically adsorbed on the surface of C80 H30 . At most six O2 molecules can be adsorbed before saturation. O2 molecule will dissociate automatically on the surface of C80 H30 when the adsorption concentration is high enough and C80 H30 will be unzipped accompanied by O2 dissociation. Therefore, C80 H30 can be used in oxygen involved reactions as a reducing agent or a sacrificial agent to remove oxygen. Furthermore, the HOMO-LUMO gap of C80 H30 can be tuned easily in a wide range via controlling the concentration and the position of O2 adsorption, which demonstrate the possibility of using C80 H30 in optoelectronics. Our results thus indicate that C80 H30 is a versatile nano-carbon material due to its distinct molecule adsorption behaviors.